The Pre-service EFL Teachers’ Voices on Designing and Implementing Lesson Plan for Online Learning - Euis Rahmawati; Hilmansyah Saefullah; Sumarta Sumarta (Edumaspul: Jurnal Pendidikan, 2021)
Designing and implementing a lesson plan is a complex process, so that according to several studies, the pre-service EFL teachers still had difficulties during designing and implementing a lesson plan. As novice designers, pre-service EFL teachers still lack of knowledge and expertise. Therefore, this study aims to find out the voices of the pre-service EFL teachers about their own experiences in designing and implementing their lesson plans. Five pre-service EFL teachers who had experienced to design and implement a lesson plan in the teaching practicum program during the Covid-19 pandemic outbreak at Senior High Schools in Karawang were recruited as the research participants. This study uses a qualitative approach and uses collective case studies research design. Online written interviews and virtual observation were conducted to collect data as information to answer the research question, and the interview data were then analyzed using thematic analysis. This research found out that designing and implementing lesson plans practiced by the pre-service EFL teachers during the teaching programs were perceived as decision-making process, non-negotiable process, and challenging process.